2006
DOI: 10.1016/j.drugalcdep.2005.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Medical and nonmedical use of prescription pain medication by youth in a Detroit-area public school district

Abstract: The purpose of this descriptive study was to examine the nonmedical use of prescription pain medications in a sample of public school students in the Detroit metropolitan area. The Web-based survey occurred during a 2-week period in May 2003 and drew on a diverse population between the ages of 10 and 18 years. An 87% response rate was achieved, providing a final sample of 1017. Twenty-two percent of girls and 10% of boys reported lifetime nonmedical use of a pain medication (χ 2 = 25.2, d.f. = 1, p < 0.001). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
164
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(182 citation statements)
references
References 15 publications
13
164
0
5
Order By: Relevance
“…To date, only a few studies have examined non-prescribed use of pain relievers among adolescents using representative population-based samples. Boyd and colleagues (2006a) examined non-prescribed use of prescription pain relievers among 1017 students in grades 5 through 10 from a Detroit-area public school district and found that 22% of females reported lifetime non-prescribed use of pain relievers compared with 10% of males (Boyd et al, 2006a). McCabe and colleagues (2007a) examined prescribed and non-prescribed medication use among 1086 students in grades 7 through 12 from a Detroit-area public school district.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only a few studies have examined non-prescribed use of pain relievers among adolescents using representative population-based samples. Boyd and colleagues (2006a) examined non-prescribed use of prescription pain relievers among 1017 students in grades 5 through 10 from a Detroit-area public school district and found that 22% of females reported lifetime non-prescribed use of pain relievers compared with 10% of males (Boyd et al, 2006a). McCabe and colleagues (2007a) examined prescribed and non-prescribed medication use among 1086 students in grades 7 through 12 from a Detroit-area public school district.…”
Section: Introductionmentioning
confidence: 99%
“…Together, the available data suggest that non-prescribed use of pain relievers is more prevalent among girls than among boys (e.g., Boyd et al, 2006a;McCabe et al, 2007a). In addition, the use of non-prescribed pain relievers may be influenced by medical exposure to pain relievers, by health conditions that could lead to non-prescribed use for self-medication purposes, and by the prior use of alcohol and other commonly used drugs (e.g., marijuana and inhalants) (Boyd et al, 2006a;McCabe et al, 2007a;Sung et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Stressors such as parents being treated for chronic pain or having their own problems with NMUPD or SU are well established risk factors for the initiation of NMUPD in adolescents (Boyd et al, 2006; Nargiso, Ballard, & Skeer, 2015; Tucker et al, 2015). Thus, when assessing the influence of this family factor on NMUPD, one would have expected stronger associations.…”
Section: Discussionmentioning
confidence: 99%
“…These different preferences have also been shown to evolve distinctly for each medication over time, further reinforcing the idea that they are chosen with specific regard to a perceived individual problem and the precise effects that the substance can have on it (McCabe, Kloska, Veliz, Jager, & Schulenberg, 2016). In addition, it is well established that NMUPD by young people often shows concomitant use of alcohol or illicit substances (Boyd, Esteban McCabe, & Teter, 2006; Ford, 2009; Kelly, Wells, Pawson, LeClair, & Parsons, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…De modo similar a lo reportado por otros investigadores, las mujeres en nuestro estudio se automedican en mayor proporción que los hombres 18,19 . Sin embargo, un estudio de Evans y Sullivan no reportaron diferencias en cuanto al sexo en la automedicación de psicofármacos 20 .…”
Section: Discussionunclassified